تصوف اور قرآن: ایک مطالعہ: A Study of Mysticism and Quran (Al-Qamar, 2023)
Mysticism is a spiritual way of living which assesses a person inertly and help to promote his special qualities. Islam guides a man to make him spiritually pure and strong person in order to establish peace and justice. Every verse of Quran has inner meaning by her existence. The Islamic mysticism is reflected by Quran and Ideal personalities.
Keywords: Mysticism; Soul; Purification; Internal; Qualities; Human; Depth